Exploração semissintética de produtos naturais contendo guaiacol na busca de novos agentes antineoplásicos - Theisen, Maria Carolina (2025)
Cancer is one of the most relevant health conditions in the world and requires the development of new therapeutic alternatives. Targeting the epigenetic mechanisms involved and the minor groove of DNA has been promising. Therefore, semisynthetic strategies with natural products are widely used to generate bioactive compounds and guaiacol-containing natural products are an attractive possibility. Thus, this work aimed to explore the reactivity of these compounds on the synthesis of potential antineoplastic agents inspired by histone deacetylase, histone lysine demethylase specific 1 and EZH2 inhibitors and also minor groove binders, and evaluate their cytotoxic activity on the breast cancer cell line MCF-7. Four series of compounds were designed: beta-aminoalcohols and Heck - from eugenol and isoeugenol, triazole - from acetovanillone, and reductive amination from vanillin. Eugenol was extracted from clove buds with 20% yield. The beta-aminoalcohol series was synthesized by epoxidation of the alkene moiety from phenylpropanoids and its ring-opening reaction with amines, resulting in 8 products from eugenol (15-70% yield). Due to problems with the reactivity of isoeugenol, was not possible to obtain the desired products from it. In the Heck reaction with eugenol was obtained a mixture of both E/Z products and byproducts, with no success in isolation. In this reaction with isoeugenol, an unexpected product occurs, the licarin A, and was aimed the optimization of this methodology, with no success yet. The triazole series was prepared with acetovanillone, amines, and p-nitrophenylazide, resulting in 7 products (63-93% yield). In the reductive amination series, only one of the desired products was obtained, but not successfully purified. Also, another unexpected product was synthesized, a benzoimidazole. The conditions will be optimized in the future. Additionally, two amidoximes were obtained from the nitrile-containing products (50-53% yield), and from a triazole derivative, two amides were synthesized employing innovative conditions that still need optimization. One of these later products also presented a challenging purification. A total of 18 final compounds were obtained and tested on the MCF-7 cell line with MTT assay, with vorinostat as a control drug. The only compound that showed an interesting antiproliferative activity (GI50 = 20,5 μM) was inspired by LSD-1 inhibitors and its promising for more studies.